STRATEGY OF TEACHING SPEAKING BY USING GAMES FOR FRONTRUNNER CLASS AT EF (ENGLISH FIRST) - Amelia, Dinda; Hidayat, Rahmad (Universitas Islam Lamongan, 2023)
Language is important in everyday life to convey various information and opinions to others. English is a key International language for communicating with other people. This research is very interesting because it explores the teaching strategy used by the teacher in an English course, namely EF English First. This research aims at explaining the teachers' strategy of teaching speaking by using games for Frontrunner class. This research uses a qualitative with case study approach where the researcher conducts an interview and observation. This study focuses on the tenth level of Frontrunner class which at the ten to twelve is Upper Intermediate level, so that included in the B2 level in the CEFR. The results of study show the students are happy and learning becomes interactive by using games in teaching speaking. Because they can add new vocabularies and can develop their ideas by doing speaking activities.